2017
DOI: 10.3354/meps12032
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of corkscrew sea anemones Bartholomea annulata in the Florida Keys

Abstract: Corkscrew sea anemones Bartholomea annulata are important ecologically as hubs of a mutualistic network involving cleaner shrimps and client fishes on Caribbean reefs. They also are collected for the ornamental aquarium trade, but little is known about their population dynamics to support conservation management. We quantified variation in population structure among regions of the Florida Keys and levels of human impact within region. The Upper Keys and lowimpact sites supported higher population abundance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 87 publications
1
6
1
Order By: Relevance
“…The average number of anemones within the radial transects was 20.4 AE 6.5 anemones. To our knowledge, the abundances of B. annulata recorded here are orders of magnitude greater than those reported byBriones- Fourzan et al (2012) andO'Reilly &Chadwick (2017), with anemone abundance at GKQ being the highest recorded density in the primary literature.…”
contrasting
confidence: 65%
See 2 more Smart Citations
“…The average number of anemones within the radial transects was 20.4 AE 6.5 anemones. To our knowledge, the abundances of B. annulata recorded here are orders of magnitude greater than those reported byBriones- Fourzan et al (2012) andO'Reilly &Chadwick (2017), with anemone abundance at GKQ being the highest recorded density in the primary literature.…”
contrasting
confidence: 65%
“…As mentioned above, a genet may be long lived even when a ramet has a short life span. Bartholomea annulata appears to fit this description: individual polyps exhibit short life spans under field conditions at St. Thomas, USVI (Nelsen 2008), and in the Florida Keys (O'Reilly & Chadwick 2017), and in laboratory aquaria (Titus 2011;O'Reilly & Chadwick 2017). Thus, genets at GKQ could undergo asexual reproduction, spread short distances in all directions (Titus 2011;O'Reilly 2015), grow, and then die.…”
Section: Locusmentioning
confidence: 88%
See 1 more Smart Citation
“…Our field experiment demonstrates that both the hermit crabs and their gastropod shells appear to possess surface coverings that prevent them from being stung by the anemones, but only for individuals that are facultative associates of this host. Sea Anemones.-The abundance of rosetip anemones, C. gigantea, at Akumal is similar to that observed at Puerto Morelos approximately 70 km north along the Yucatán Peninsula (Briones-Fourzán et al 2012), and is within the range of abundances documented for other large sea anemones on coral reefs (Chadwick and Arvedlund 2005, Dixon et al 2014, O'Reilly and Chadwick 2017. The local abundance of rosetip anemones suggests that this population may not currently be exhibiting signs of stress, and their size class distribution indicates many small individuals, which potentially are recent recruits.…”
Section: Discussionsupporting
confidence: 72%
“…For each sea anemone observed inside the belt transects, the following information was collected: species (identified using Humann and DeLoach 2006), type of substrate (categorized as sand, seagrass, or reef), distance to nearest neighboring conspecific (for individuals <1 m away), and linear dimensions [tentacle crown length (L) and width (W) for calculation of tentacle crown surface area (TCSA) = (L/2*W/2)*π; following Hirose 1985, Roopin and Chadwick 2009, O'Reilly and Chadwick 2017. Each sea anemone also was examined carefully for the presence of crustacean symbionts, and the following information was collected for all crustaceans <10 cm distant from the anemone (maximum distance of regular associates from Caribbean sea anemones, Briones-Fourzán et al 2012): crustacean species (identified using Colin 1978, Humann andDeloach 2006), number of individuals per species, body size of each individual [shrimps: total length including carapace and abdomen, which correlates with carapace length (Chakravarty and Ganesh 2014); crabs: width of carapace, except for hermit crabs, see below], and microhabitat zone occupied on the anemone (1: under tentacle crown along the anemone column, 2: inner half of tentacle crown, 3: outer half of tentacle crown; Fig.…”
Section: Studymentioning
confidence: 99%